1997
DOI: 10.1093/humrep/12.suppl_1.6
|View full text |Cite
|
Sign up to set email alerts
|

Adrenergic regulation of adipocyte metabolism

Abstract: Five adrenoceptor (AR) subtypes (beta 1, beta 2, beta 3, alpha 2 and alpha 1), are involved in the control of white and brown fat cell function. A number of metabolic events are controlled by the adrenergic system in fat cells. The stimulatory effect of catecholamines on lipolysis and metabolism is mainly connected to increments in cAMP levels, cAMP protein kinase activation and phosphorylation of various target proteins. Norepinephrine and epinephrine operate through differential recruitment of alpha 2- and b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
84
0
4

Year Published

2000
2000
2020
2020

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 117 publications
(95 citation statements)
references
References 69 publications
7
84
0
4
Order By: Relevance
“…After isoproterenol stimulation of the ␤2AR, the G␣-subunit G␣ s , through exchange of GTP for GDP, activates adenylyl cyclase, generating cyclic adenosine monophosphate (cAMP). In the adipocyte, cAMP activates protein kinase A, which, in turn, phosphorylates and activates hormone-sensitive lipase, the rate-limiting enzyme for triglyceride hydrolysis (3).…”
Section: Medical Sciencesmentioning
confidence: 99%
“…After isoproterenol stimulation of the ␤2AR, the G␣-subunit G␣ s , through exchange of GTP for GDP, activates adenylyl cyclase, generating cyclic adenosine monophosphate (cAMP). In the adipocyte, cAMP activates protein kinase A, which, in turn, phosphorylates and activates hormone-sensitive lipase, the rate-limiting enzyme for triglyceride hydrolysis (3).…”
Section: Medical Sciencesmentioning
confidence: 99%
“…The effects on cAMP production and cAMP-related cellular responses are mediated through the control of adenylyl cyclase activity by the stimulatory b 1 -, b 2 -and b 3 -adrenoceptors (AR) and the inhibitory a 2 -ARs. 1,2 The b 3 -AR is highly expressed in rodent adipose tissues 3,4 and several studies have suggested that it plays a signi®cant role in adipocyte metabolism and might be involved in the development of obesity, 4 ± 6 thus making b 3 -AR a possible target for anti-obesity drugs. In this way, numerous selective b 3 -AR agonists have been synthesized and have been found to possess, with various degrees of speci®city, anti-obesity and also anti-diabetic properties.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, DAG is hydrophobic and remains in the membrane, acting as a signal messenger for activation of protein kinase C (PKC), and facilitates its translocation to the cellular membrane. DAG-mediated PKC activation in adipocytes through b-adrenergic receptors, in turn, increases glycogenolysis and gluconeogenesis (Lafontan et al, 1997).…”
Section: Dagmentioning
confidence: 99%